Synthesis Pengo System plates for the treatment of long-bone diaphyseal fractures in dogs - Rahal, C. [UNESP]; Otoni, C. C. [UNESP]; Pereira-Junior, O. C. M. [UNESP]; Blum, A. L. L.; Vulcano, Luiz Carlos [UNESP] (Schattauer Gmbh-verlag Medizin Naturwissenschaften, 2008)
A Brazilian orthopaedic company designed a stainless steel plate called Synthesis Pengo System (S.P.S.), which has one fixed and one changeable extremity. According to the assembly of the changeable extremity, it is possible to obtain dynamization or neutralization of the fracture site. Since the S.P.S. plate was developed for use in human patients, the aim of this study was to evaluate this system in long-bone diaphyseal fractures in dogs. Eight dogs with closed diaphyseal fractures of the femur (n = 1), radius and ulna (n = 5), and tibia (n = 2) were used. Patients were aged seven months to three years and weighed 18 to 31.2 kg. The S.P.S. plate was assembled with one fixed extremity and one changeable extremity in dynamization mode. The trail bar was positioned for synthesis modules with holes for cortical screws. The modules were positioned close to one another in two fractures and for away from the fracture site in the others. The bone healing occurred by external callus. Since motion at the fracture site determines the amount of callus required, the secondary bone healing that was observed in all of the cases indicated less rigid fixation of this system. A potential benefit of this system was a lesser interface contact with the bone since it was only done by trail bar. The major disadvantage was the prominence of the implant. It was possible to conclude that the S.P.S. plate appears to be a suitable method for the treatment of diaphyseal fractures in dogs.
Keywords: fracture; treatment; plate; dogs; SPS